Connectivity in Criminal Procedure Law - L. Alfies Sihombing; Sahat Maruli Tua Situmeang; Yeni Nuraeni (INFOKUM, 2023)
In the criminal justice system, efficiency and justice are often two sides of a coin that are difficult to unite. Koneksitas is a mechanism in criminal procedure law that regulates court procedures for criminal offences, where the case falls within the jurisdiction of two different judicial institutions, namely the General Court and the Military Court. This research aims to explore how this concept can be adapted and applied in the modern legal context, taking into account the need for efficiency of the legal process and justice for all parties involved. The research method used is normative juridical. The result of this research is that connectivity court in Indonesia, regulated in KUHAP and related regulations, is important to handle cross-jurisdictional cases efficiently and consistently, but needs to maintain the rights of the defendant. KUHAP reforms and legal adaptations are needed to address these challenges, improve the legal system, and strengthen public trust. Managing inter-agency and cross-sectoral relationships within the justice system is key to ensuring fairness and integrity in law enforcement.